Extensive Reading from Students’ Perspective - Adwind Abrar; Atti Herawati; Tina Priyantin (FKIP UNIVERSITAS PAKUAN, 2021)
Extensive reading is broadly known as reading for enjoyment and is beneficial for EFL students. However, nowadays, the growth of technology has become a matter for students to be reading less than they should be. Thus, this research focused on the online extensive reading as the course program the students had experience in Pakuan University to find out their perspective. The respondents were 15 students from sixth-semester students who had experienced the Online Extensive Reading subject. The research was conducted by using qualitative method and using questionnaires and one-on-one interviews as the instruments. Data collected were separated into three indicators, which included the learning process, students’ skills improvement, and personal factors. Based on the result, the students’ perspective on the Online Extensive Reading helped them improve, especially in vocabulary gained, reading interest and reading comprehension. On the other hand, most students perceived that the learning process was effective for them to learn in this Online situation. However, they suggested that they needed more virtual meeting sessions instead of using chat forum to discuss or share. Furthermore, there were a few students that didn’t feel the effectiveness of the Online Extensive Reading because they had a problem in their personal characteristic such as, procrastinating, unmotivated to read, unmanageable time, and their lack of reading interest.